Behavior of Nonplastic Silty Soils under Cyclic Loading - Nazile Ural; Zeki Gunduz (The Scientific World Journal, 2014)
The engineering behavior of nonplastic silts is more difficult to characterize than is the behavior of clay or sand. Especially, behavior of silty soils is important in view of the seismicity of several regions of alluvial deposits in the world, such as the United States, China, and Turkey. In several hazards substantial ground deformation, reduced bearing capacity, and liquefaction of silty soils have been attributed to excess pore pressure generation during dynamic loading. In this paper, an experimental study of the pore water pressure generation of silty soils was conducted by cyclic triaxial tests on samples of reconstituted soils by the slurry deposition method. In all tests silty samples which have different clay percentages were studied under different cyclic stress ratios. The results have showed that in soils having clay content equal to and less than 10%, the excess pore pressure ratio buildup was quicker with an increase in different cyclic stress ratios. When fine and clay content increases, excess pore water pressure decreases constant cyclic stress ratio in nonplastic silty soils. In addition, the applicability of the used criteria for the assessment of liquefaction susceptibility of fine grained soils is examined using laboratory test results.